Relationship of Knowledge and Attitude Towards Stunting Prevention Behavior in Adolescent Girls - Azzahra, Shafira; Sukmawati, Sukmawati; Witdiawati, Witdiawati (Indonesian Journal of Global Health Research, 2024)
Stunting is a serious public health problem that affects children's physical growth and cognitive development. Adolescent girls have an important role in preventing stunting through their knowledge and attitudes. This study aims to determine the relationship between the knowledge and attitudes of adolescent girls towards stunting prevention behavior at SMA Mekar Arum. The research method used is a quantitative correlation. The research sample was taken using a total sampling method which amounted to 130 adolescent girls who attend SMA Mekar Arum. The research instrument was a questionnaire that included aspects of knowledge about stunting, attitudes towards stunting prevention, and stunting prevention behavior. The data obtained were analyzed using univariate and bivariate analysis with the Spearman Rank statistical test obtained a p-value of 0.061 (p-value > 0.05) for the knowledge variable and a p-value of 0.000 (p-value < 0.05) for the attitude variable. There was no significant relationship between knowledge and stunting prevention behavior, but there was a significant relationship between attitudes and stunting prevention behavior at SMA Mekar Arum.